FEATURES OF HEMOSTASIS IN RHEUMATOID ARTHRITIS PATIENTS WITH ISCHEMIC HEARTH DISEASE - Shadjanova N. S. (International Engineering Journal For Research & Development, 2022)
As in the developed countries of the world, a number of scientific studies in the field of RA and AS have been carried out in recent years. Rheumatoid arthritis (RA) remains the focus of researchers due to its multifactorial origin, complex and completely unclear pathogenesis. This article presents materials on the effect of rheumatoid arthritis (RA) on the parameters of the hemostasis system in patients with coronary heart disease. In order to study this work, 86 RA patients with associated CAD were examined, and hemostasis parameters were compared with the RA group without CAD, which consisted of 40 patients. The influence of age, gender, RA disease activity on hemostasis parameters in this category of patients was analyzed.